Analysis of the Social-economic Factors that Facilitate Small, Micro, Medium Farming Enterprises (SMMEs) in South Africa - Victor M. Mmbengwa; Xiaoshun Qin (An Overview on Business, Management and Economics Research Vol. 3, 2023)
This study investigated the potential of farming small, micro, medium enterprise (SMMEs) to contribute to the resolve of socio-economic problems. Land reform is a form of agrarian reform involving the changing of laws, regulations, or customs regarding land ownership. Land reform may consist of a government-initiated or government-backed property redistribution, generally of agricultural land. Land reform can, therefore, refer to transfer of ownership from the more powerful to the less powerful, such as from a relatively small number of wealthy or noble owners with extensive land holdings (e.g., plantations, large ranches, or agribusiness plots) to individual ownership by those who work the land. Such transfers of ownership may be with or without compensation; compensation may vary from token amounts to the full value of the land. South Africa is one of the developing countries with high prevalence of socio-economic challenges, such as high levels of joblessness, poverty, food iinsecurity and malnutrition, particularly among rural and peri-urban poor people. Since 1994, the South African government has had a goal that the farming sector should play an important role in food security, job creation and wealth creation. Both qualitative and quantitative research methodologies were employed in this study, with the former relying on participatory forums, where the data was taken with the aid of video recordings, whilst the later methodology used semi-structured questionnaire. The quantitative data obtained and used in this study were gathered from year 2006 to2007. This information was gathered by extension staff from a sample size of 1873 agricultural SMMEs (20% of the registered farming SMMEs in the nine provinces of South Africa). In order to increase the likelihood that the SMMEs created in the agricultural sector will help to address socioeconomic problems, it is necessary to innovate and investigate mechanisms that can turn micro and small businesses into medium-sized businesses. It appears that the majority of these SMMEs lack the capacity to be sustainable.